Gender, Pengetahuan Keuangan, dan Niat Bertansaksi Saham - Nurhidayah, Nurhidayah (LP2M Institut Teknologi dan Bisnis Asia Malang, 2018)
This study aims to examine the influence of financial knowledge on gender relations and the intentions of individual investor transactions in the Indonesian capital market. Given the high number of passive investors in Indonesia it is important to know the influence to improve understanding of financial knowledge, especially about stocks. Test method using Moderated Regression Analysis (MRA) with a sample of 41 individual investors who conduct transactions selling and buying shares. The results showed that gender has no significant effect on transaction intention. The interaction variables gender* transaction intentions have a positive and significant effect on the transaction intent. This implies the importance of improving the understanding of investors' financial knowledge in order to generate the intention to transact shares.